Bioekonomi — mellan människa och ting - Åkesson, Lynn (Kulturella Perspektiv – Svensk etnologisk tidskrift, 2001)
Taking out patents from biological, human tissues often raises debate. Why is that? Answers to these, and similar questions, are often formulated from an ethical point of view. In this article cultural perspectives are used to reflect on patents. Relying on Igor Kopytoff's article The cultural biography of things: commoditization as process, I argue that the unease associated with patents has to do with the wish to keep a strict borderline between people and things. This borderline is constantly blurred since bio-economics, new economic niche created by the success of bio-technology, operates precisely in the border area between people and things. It nurtures from human materials that are reshaped into commodities in a commercial markets. The concept of patent represents bio-economy in a symbolic way, compressing the multiples consequences of this economy.